High-performance supercapacitor energy storage using a carbon material derived from lignin by bacterial activation before carbonization. Issue 47 (29th August 2019) - Zhang, Kejing; Liu, Mingren; Zhang, Tingzheng; Min, Xiaoye; Wang, Zhongren; Chai, Liyuan; Shi, Yan
Abstract : A novel green bacterial activation method for the synthesis of a lignin derived carbon material with excellent electrochemical performances. Abstract : The conversion of low-cost renewable lignin could enable the economic fabrication of carbon materials for energy storage devices. However, the traditional activation methods for the production of a lignin-derived porous carbon with a large specific surface area are complex and expensive, and some activators can cause pollution. In this paper, we propose a novel green bacterial activation method for the synthesis of a carbon material with a large surface area of up to 1831 m 2 g −1 and abundant micropores and mesopores through a conventional carbonization procedure with a simple bacterial culture process. The transformation of the lignin structure by the bacteria optimizes the pore structure of the derived carbon and promotes graphitization. Consequently, as an electrode in a supercapacitor, the obtained material exhibits a very high specific capacitance (428 F g −1 at 1 A g −1 ), high cycling stability (capacitance retention of 96.7% after 10 000 cycles at 5 A g −1 ), and superior rate performance in an aqueous electrolyte. In addition, the symmetric supercapacitor based on the bacteria-activated lignin-derived carbon exhibits a superior energy density of 66.18 W h kg −1 at 312 W kg −1 in an ionic liquid electrolyte system. These excellent features demonstrate the large potential of the developed material for applications in high-performance supercapacitors. Furthermore, the proposed bacteria-activation method can guide a novel bio-modification for material syntheses.